(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To characterize oocyte maturation status and investigate clinical factors influencing oocyte maturity in controlled ovarian stimulation cycles for in vitro fertilization (IVF). Materials and Methods: This retrospective descriptive study analyzed 139 IVF cycles utilizing a GnRH antagonist protocol at the Center of IVF and Tissue Engineering, Hanoi Medical University Hospital, between January 2023 and June 2024. Data regarding oocyte developmental stage, ovarian stimulation parameters, and fertilization outcomes were systematically collected and evaluated. Results: Mature oocytes at the metaphase II (MII) stage constituted 65.81 ± 17.92% of the total oocytes retrieved, whereas immature oocytes at the metaphase I (MI) and germinal vesicle (GV) stages accounted for 9.2 ± 11.18% and 6.88 ± 10.55%, respectively. The intracytoplasmic sperm injection (ICSI) rate was 69.36 ± 17.64%, with a corresponding fertilization rate of 88.29 ± 18.03%. Prolonged duration of infertility and lower initial doses of recombinant FSH were significantly associated with an increased proportion of immature oocytes (p = 0,001 and p = 0,022, respectively). In contrast, a longer duration of ovarian stimulation was positively correlated with higher oocyte maturation rates (p = 0,031). No statistically significant associations were observed between oocyte maturity and patient age, anti-Müllerian hormone (AMH) levels, body mass index (BMI), or serum concentrations of LH, estradiol, and progesterone at the time of trigger. Conclusion: The degree of oocyte maturation in IVF cycles appears to be influenced by modifiable clinical variables, particularly the duration of infertility, the initial FSH dosage, and the length of ovarian stimulation. Further large-scale studies are needed to elucidate the role of these factors in optimizing oocyte quality and enhancing clinical outcomes.